DEVELOPMENT OF PROFESSIONAL- PEDAGOGICAL CREATIVITY OF FUTURE PHYSICAL EDUCATION TEACHERS BASED ON A COMPETENT APPROACH (American Journal of Pedagogical and Educational Research, 2025)
It aims to train talented, free and creative thinkers, capable of conveying their vision to the community and collective, qualified, and at the same time well-developed personal and professional qualities, who can provide the Republic of Uzbekistan with modern education and technologies for tomorrow and the future. The main goal of the education system is to train specialists who can quickly master the accelerating globalization process of the world's nations, not lose their place in the trade market, and ensure the stability of the nation.